Evidence consistent with the requirement of cresolase activity for suicide inactivation of tyrosinase. - Land, E; Ramsden, C; Riley, P; Stratford, MR (2008)
Tyrosinase is a mono-oxygenase with a dinuclear copper catalytic center which is able to catalyze both the ortho-hydroxylation of monophenols (cresolase activity) and the oxidation of catechols (catecholase activity) yielding ortho-quinone products. Tyrosinases appear to have arisen early in evolution and are widespread in living organisms where they are involved in several processes, including antibiosis, adhesion of molluscs, the hardening of the exoskeleton of insects, and pigmentation. Tyrosinase is the principal enzyme of melanin formation in vertebrates and is of clinical interest because of the possible utilization of its activity for targeted treatment of malignant melanoma. Tyrosinase is characterised by an irreversible inactivation that occurs during the oxidation of catechols. In a recent publication we proposed a mechanism to account for this feature based on the ortho-hydroxylation of catecholic substrates, during which process Cu(II) is reduced to Cu(0) which no longer binds to the enzyme and is eliminated (reductive elimination). Since this process is dependent on cresolase activity of tyrosinase, a strong prediction of the proposed inactivation mechanism is that it will not be exhibited by enzymes lacking cresolase activity. We show that the catechol oxidase readily extracted from bananas (Musa cavendishii) is devoid of cresolase activity and that the kinetics of catechol oxidation do not exhibit inactivation. We also show that a species with the molecular mass of the putative cresolase oxidation product is formed during tyrosinase oxidation of 4-methylcatechol. The results presented are entirely consistent with our proposed mechanism to account for suicide-inactivation of tyrosinase.